2022
DOI: 10.1371/journal.pone.0270372
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity analysis of shotgun metagenomic reads describes gut microbiome development and treatment effects in the post-weaned pig

Abstract: Intensive farming practices can increase exposure of animals to infectious agents against which antibiotics are used. Orally administered antibiotics are well known to cause dysbiosis. To counteract dysbiotic effects, numerous studies in the past two decades sought to understand whether probiotics are a valid tool to help re-establish a healthy gut microbial community after antibiotic treatment. Although dysbiotic effects of antibiotics are well investigated, little is known about the effects of intramuscular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…In addition to identification of commensal bacteria typically associated with healthy swine, we identified pathogenic species that can cause illness and physiological changes in the animal’s gastrointestinal tract. These micro-organisms can also be shed into the environment, presenting a potential threat to public health [20, 21]. While other, non-bacterial microbial pathogens can also infect farmed pigs [37, 38], we did not identify a high proportion of non-bacterial DNA in our samples, however eukaryotic pathogen databases are poorly populated and represents an opportunity that could be reassessed in future studies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition to identification of commensal bacteria typically associated with healthy swine, we identified pathogenic species that can cause illness and physiological changes in the animal’s gastrointestinal tract. These micro-organisms can also be shed into the environment, presenting a potential threat to public health [20, 21]. While other, non-bacterial microbial pathogens can also infect farmed pigs [37, 38], we did not identify a high proportion of non-bacterial DNA in our samples, however eukaryotic pathogen databases are poorly populated and represents an opportunity that could be reassessed in future studies.…”
Section: Discussionmentioning
confidence: 92%
“…In swine, shotgun metagenome analyses have also been applied to investigate the antimicrobial and heavy metal resistance genes harboured in fattening swine caecal microbiomes, as well as the effect probiotic supplementation has on piglet health [17,18]. While previous studies have shown that caecal microbiomes are diverse and can be correlated with high feed efficiency and utilization [9,19], few studies have utilized the intestinal scraping technique to study micro-organisms directly interacting with the host, particularly in swine [20,21]. In this study, a shotgun metagenome approach was implemented to thoroughly investigate and characterize the pathogenic and commensal bacteria harboured in the swine gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid bacteria are commonly used for the preservation of food and animal feed. Lactic acid bacteria are extensively employed in silage because of their potential to speed up lactic acid formation, lower pH, prevent protein breakdown, minimize dry matter (DM) loss, and improve animal performance [ 11 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…They also create lactic acid, organic acids, hydrogen peroxide, and bacteriocins [ 11 ]. Finally, the generation of lactic acid during lactic acid fermentation significantly lowers the pH, which appears to inhibit the growth of Gram-negative pathogenic bacteria [ 12 , 13 ]. When forecasting the effectiveness of fermentation and deciding whether to apply bacterial inoculants to silage, the quantity and features of LAB have grown to be a crucial consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Given an appropriate selection of reference sequences for the query sequences under consideration, phylogenetic placement is a valuable tool in phylogenetics and metagenomics: The major application of phylogenetic placement has been the identification of short metataxonomic read sequences [470][471][472]. Here, placement results provide information on the identity and evolutionary context of short sequencing reads.…”
Section: Applications Of Phylogenetic Placementmentioning
confidence: 99%